Research Methodologies in Architectural Studies: A Comprehensive Review - Avanti Gole,; Anita Meskar, (AG Volumes, 2025)
This review focuses on the research methodology in architectural studies such as the shift by traditional design-based approaches to evidence-based and interdisciplinary and technology-oriented frameworks. It addresses qualitative, quantitative and mixed research methodologies and how they are applied in the interpretation of social, environmental, technical and human centric elements of built environment. The review also examines some of the new trends like artificial intelligence, the construction of information modeling, parametric design, data-driven performance analysis, and immersive technologies. The focus is put on sustainability, resilience, and occupant well-being and implies that robust and hybrid approaches should be used to cope with the complex issues of architecture in current research and practice.